A framework for complexity in palliative care: A qualitative study with patients, family carers and professionals. (June 2018) - Pask, Sophie; Pinto, Cathryn; Bristowe, Katherine; van Vliet, Liesbeth; Nicholson, Caroline; Evans, Catherine J; George, Rob; Bailey, Katharine; Davies, Joanna M; Guo, Ping; Daveson, Barbara A; Higginson, Irene J; et al.
Background: Palliative care patients are often described as complex but evidence on complexity is limited. We need to understand complexity, including at individual patient-level, to define specialist palliative care, characterise palliative care populations and meaningfully compare interventions/outcomes. Aim: To explore palliative care stakeholders' views on what makes a patient more or less complex and insights on capturing complexity at patient-level. Design: In-depth qualitative interviews, analysed using Framework analysis. Participants/setting: Semi-structured interviews across six UK centres with patients, family, professionals, managers and senior leads, purposively sampled by experience, background, location and setting (hospital, hospice and community). Results: 65 participants provided an understanding of complexity, which extended far beyond the commonly used physical, psychological, social and spiritual domains. Complexity included how patients interact with family/professionals, how services' respond to needs and societal perspectives on care. 'Pre-existing', 'cumulative' and 'invisible' complexity are further important dimensions to delivering effective palliative and end-of-life care. The dynamic nature of illness and needs over time was also profoundly influential. Adapting Bronfenbrenner's Ecological Systems Theory, we categorised findings into the microsystem (person, needs and characteristics), chronosystem (dynamic influences of time), mesosystem (interactions with family/health professionals), exosystem (palliative care services/systems) and macrosystem (societal influences). Stakeholders found it acceptable to capture complexity at the patient-level, with perceived benefits for improving palliative care resource allocation. Conclusion: Our conceptual framework encompasses additional elements beyond physical, psychological, social and spiritual domains and advances systematic understanding of complexity within the context of palliative care. This framework helps capture patient-level complexity and target resource provision in specialist palliative care.